Suicidality Related to the COVID-19 Lockdown in Romania: Structural Equation Modeling - Panfil, Anca-Livia; Lungeanu, Diana; Tamasan, Simona; Bredicean, Cristina; Papava, Ion; Smirnova, Daria; Fountoulakis, Konstantinos N. (Frontiers in Psychiatry, 2022)
Background Suicidality is a serious public health concern at a global scale. Suicide itself is considered to be preventable death; worldwide, suicide rates and their trends are under constant scrutiny. As part of the international COMET-G cross-sectional study, we conducted a national level investigation to examine the individual disturbances (such as anxiety, depression, or history of life-threatening attempts) and contextual factors (such as adherence to conspiracy theories or Internet use) associated with suicidality related to the COVID-19 lockdown in a lot of Romanian adults. Participants and Methods One thousand four hundred and forty-six adults responded to an anonymous on-line questionnaire, with mean age ± standard deviation of 47.03 ± 14.21 years (1,142 females, 292 males, 12 identified themselves as non-binary). Data were analyzed using descriptive statistics and structural equation modeling (SEM). Results Univariate analysis showed strong significant correlation between anxiety and depression scorings among the respondents (Spearman R = 0.776, p < 0.001). Both the suicidality scorings and the Internet use correlated fairly with anxiety and depression, with two-by-two Spearman coefficients between R = 0.334 and R = 0.370 (p < 0.001 for each). SEM analysis substantiated the emotional disturbances, previous life-threatening attempts, and younger age as significant predictors for suicidality. The patterns of reality reading (including religious inquiries, Internet use, and beliefs in conspiracy theories) did not reach the statistical significance as influential factors in the suicidality of these respondents. There was no covariance between the Internet use and belief in conspiracy theories. Conclusion The study confirmed the suicidality risk initially hypothesized as being associated with the history of life-threatening attempts, increased depression within the younger population, and higher anxiety during the first year of the COVID-19 pandemic and its related lockdown. National strategies for effective interventions at various levels of the healthcare system should be developed.